1995
DOI: 10.1021/es00006a020
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Kinetics of Phosphate Release from Soil

Abstract: Long-term phosphate (P) desorption from soil is described using two discrete P "pools" in the soil: one available and one strongly fixed pool. The P release kinetics for each pool are described with a firstorder rate equation. A new desorption method is used with hydrous iron oxide inside dialysis tubing acting as a P sink. The widely used iron-impregnated filter paper desorption method overestimates initial P desorption by a factor of up to 4 and underestimates the quantitative progression of desorption as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
114
5

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(127 citation statements)
references
References 17 publications
8
114
5
Order By: Relevance
“…pool will increase (Lookman et al 1995b). This has been confirmed by many studies reporting a significant positive relationship between soil P solubility and saturation index ( Table 1).…”
Section: M3p/x M M3p/alm3mentioning
confidence: 99%
See 1 more Smart Citation
“…pool will increase (Lookman et al 1995b). This has been confirmed by many studies reporting a significant positive relationship between soil P solubility and saturation index ( Table 1).…”
Section: M3p/x M M3p/alm3mentioning
confidence: 99%
“…Similarly, Van der Zee et al (1988) reported that "the degree of saturation of soil with P may be expressed with the ratio α = F/ME", in which F may be assessed with P ox and ME = Al ox + Fe ox (expressed in mmol kg -1 ). Lookman et al (1995b) also refered to the molar ratio of P ox /(Al ox + Fe ox ) as an estimator for the initial degree of P saturation of the binding sites in slightly acidic to acidic sandy soils.…”
mentioning
confidence: 99%
“…In contrast, for soil under R14 plantation longer period is expected to complete the desorption process. As noted by Lookman et al [96], for sandy soils with low sum of Fe ox and Al ox , the P desorption attains more than 90% of P ox on a long time scale (200 days). The Spearman correlation shows significant ( < 0.01) negative correlation between all investigated sites and the Fe ox and Al ox .…”
Section: Soil P Sorption Kineticsmentioning
confidence: 68%
“…Moreover, by using a sink with concentration gradient, the desorption process is forced, and it is independent of extraction solution. However, the desorption amount based on this technique may tend to overestimate the initial desorbed P or underestimate the quantitative progression of desorption, leading to the impression that desorption stability level is reached after some time [96]. Additionally, the adhesion of fine soil particles to the paper strips can cause adsorption errors.…”
Section: Soil P Sorption Kineticsmentioning
confidence: 99%
“…Both Al ox and Fe ox are important sorbents for phosphate and other anions (Freese et al 1992;Lookman et al 1995;Kanˇa and Kopa´cˇek 2006) and soils with high Al ox and Fe ox concentrations have a high capacity for P sorption (Yuan and Lavkulich 1994). Decreasing soil pH also increases the positive charge around Al and Fe oxides and thereby increases anion adsorption (Muljadi et al 1966;Bowden et al 1980).…”
Section: Patterns In Stream Total Phosphorusmentioning
confidence: 99%